LABOUR /GOVERNMENT RELATIONS IN NIGERIA: A STUDY OF REGULATION (1999 – 2012) - Abdulrahman, Ndajiya; Mato, Kabir (European Scientific Journal, ESJ, 2014)
The study was conducted primarily to investigate labour/government relations in Nigeria: A Study of Regulation, 1999 – 2012. The study is guided by four research questions. The population of the study comprises of all the 500 workers and government officials in the selected areas of study. Frequency count, percentage and statistical mean were used to analyze the results. The finding of the study reveals that, the respondents accepted all the impact of trade unionism and collective bargaining on Nigeriadevelopment.That is, Trade union and collective bargaining contributed to, Economic development in Nigeria, Provision of infrastructural development such as water, electricity, road and schools facilities, Provide the knowledge of laws that regulate labour activities in Nigeria, Improve Capacity building of workers, education, finance and independent, Guarantee workers salary, Protection of workers right and personnel interest, Boost worker physical integrity and moral dignity of the individual and Prevent workers being threaten or dismissed without reasons; the finding also reveals that the respondents, responded positively to the perceived causes of strike actions in Nigeria; that is, Poor infrastructural Development, High rate of corruption, Failure to implement collective agreement such as harmonized salary structure, Military intervene into democracy, Refusal to ascend to union, Poor or Delay in salary and wages of worker, Dissolution of trade union to segment to reduce their power, Retrenchment and unemployment problems and Strike may call back without consulting member. Similarly, the finding also reveals that the respondents accepted, all the items on reasons why successive and present governments subvert labour movement activities in Nigeria; that is, Military government demoralize union right, Problems of internal democracy is a threat to trade unionism, Both military and political leaders bane or arrest and even imprisons labour leaders, Regularism of trade union act pose a problems and Fear and apathy created in worker through unending rationalization retrieval of workers wages salary cuts. Finally, the finding reveals that the respondents, responded positively to the measures/strategies to regulate labour movement; that is, Nigerian workers must fight and dement the right at all times, Government should provide basic amenities such as water, electricity, improve agriculture and basic education to Nigerian, Improve salary structure and wages, Government in all level must fight corrupt leaders, Immunity clause should be removed in the constitution of the federal republic of Nigeria to tried corrupt leaders, Government should protect the right of workers, Prompts payment of salary and arrears to person and retired workers, There should be rule of law and due processes, Provision of employment opportunities and Employers should not victimize workers.